Comprehensive Flavor Analysis of Volatile Components During the Vase Period of Cut Lily (Lilium spp. ‘Manissa’) Flowers by HS-SPME/GC–MS Combined With E-Nose Technology - Wei, Lijuan; Wei, Shouhui; Hu, Dongliang; Feng, Li; Liu, Yayu; Liu, Huwei; Liao, Weibiao (Frontiers in Plant Science, 2022)
Volatile compounds could affect the flavor and ornamental quality of cut flowers, but the flavor change occurring during the vase period of cut flower is unclear. To clarify the dynamic changes during the vase period of cut lily (Lilium spp. ‘Manissa’) flowers, comprehensive flavor profiles were characterized by electronic nose (E-nose) and headspace solid-phase microextraction gas chromatography-mass spectrometry (HS-SPME/GC-MS). The response value of sensor W2W was significantly higher than other sensors and its response value reached the highest on day 4. A total of 59 volatiles were detected in cut lilies by HS-SPME/GC-MS, mainly including aldehydes, alcohols and esters. There were 19 volatiles with the odour activity values (OAVs) greater than 1. Floral and fruity aromas were stronger, followed by pungent scent. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) could effectively discriminate lily samples derived from different vase time on the basis of E-nose and HS-SPME-GC-MS. In summary, our study investigated the flavor change profile and the diversity of volatile compounds during the vase period of cut lilies, and lilies on day 4 after harvest exhibited excellent aroma and flavor taking into consideration of the flavor intensity and diversity. This provided a theoretical guidance for the assessment of scent volatiles and flavor quality during the vase period of cut lily flowers and will be helpful for the application of cut lilies during postharvest process.